Flexor tendon injuries: Repair & Rehabilitation. Issue 8 (August 2021) - Pearce, Oliver; Brown, Matthew T; Fraser, Katrina; Lancerotto, Luca
Abstract: Flexor tendon injuries are common and occur mostly by penetrating trauma. Suspected flexor tendon injuries require a thorough clinical assessment and often are not isolated injuries. A detailed understanding of flexor tendon anatomy and spatial relationships is essential, especially when repairing multi-tendon injuries. Principles of flexor tendon repair include a strong suture construct, minimising gap formation between tendon ends, preserving tendon blood supply and providing a smooth repair interface. Moreover, adequate exposure of the zone of injury using full-thickness skin flaps and preservation of neurovascular and pulley structures is essential. In this article an overview of contemporary management strategies is presented. Today's hand surgeons and therapists can choose from a variety of treatment options when managing these important and potentially life-changing injuries.